Genotyping of Sumatera local variety of citrus using random amplified polymorphism DNA (RAPD) technique - Sari, Rinti Mutiara; Achyar, Afifatul A; Ahda, Yuni; Hilda Putri, Dwi (Genetikawan Muda Indonesia, 2022)
Indonesia has local varieties of citrus that are no less than imported citrus, especially in terms of fruit freshness. However, people are more interested in the color of citrus peel so people prefer imported citrus to local citrus, especially in Sumatera. Therefore, it is necessary to carry out efforts to conserve and improve the characteristics of these citrus to improve their quality through plant breeding. This study aims to optimize DNA isolation methods for citrus fruit samples with Chelex-TE and to determine the genetic profile of local Sumatera citrus and imported citrus using the genotyping RAPD. The samples used were several local citrus in Sumatera (Citrus Siam Mountain Omeh, Citrus Madu, Citrus Keprok Maga, Citrus Keprok Brastepu and Citrus Pasaman) and imported Citrus (Citrus Sunkist, Citrus Clemengold, Citrus Murkot and Citrus Wokam). DNA was isolated using the 10% Chelex-TE method which was optimized for several parameters such as grain size, fruit skin and leaves. RAPD was performed using 10 RAPD primers. The results showed that the optimum 10% Chelex Chelex-TE isolation method was a sample size of 1 grain. The amplification of local Sumatran citrus and imported citrus using 10 single primers produced polymorphic bands. The value of jaccard's similarity indicates that the five samples of Sumatera local variety of citrus and imported citrus have high genetic variation. Indonesia has local varieties of citrus that are no less than imported citrus, especially in terms of fruit freshness. However, people are more interested in the color of citrus peel so people prefer imported citrus to local citrus, especially in Sumatera. Therefore, it is necessary to carry out efforts to conserve and improve the characteristics of these citrus to improve their quality through plant breeding. This study aims to optimize DNA isolation methods for citrus fruit samples with Chelex-TE and to determine the genetic profile of local Sumatera citrus and imported citrus using the genotyping RAPD. The samples used were several local citrus in Sumatera (Citrus Siam Mountain Omeh, Citrus Madu, Citrus Keprok Maga, Citrus Keprok Brastepu and Citrus Pasaman) and imported Citrus (Citrus Sunkist, Citrus Clemengold, Citrus Murkot and Citrus Wokam). DNA was isolated using the 10% Chelex-TE method which was optimized for several parameters such as grain size, fruit skin and leaves. RAPD was performed using 10 RAPD primers. The results showed that the optimum 10% Chelex Chelex-TE isolation method was a sample size of 1 grain. The amplification of local Sumatran citrus and imported citrus using 10 single primers produced polymorphic bands. The value of jaccard's similarity indicates that the five samples of Sumatera local variety of citrus and imported citrus have high genetic variation.